Gibberellins as a novel mutagen for inducing 2n gametes in plants - Zhao, Yifan; Kong, Bo; Do, Phuong Uyen; Li, Liang; Du, Jiahua; Ma, Lexun; Sang, Yaru; Wu, Jian; Zhou, Qing; Cheng, Xuetong; Kang, Xiangyang; Zhang, Pingdong (Frontiers in Plant Science, 2023)
The plant hormone gibberellin (GA) regulates many physiological processes, such as cell differentiation, cell elongation, seed germination, and the response to abiotic stress. Here, we found that injecting male flower buds with exogenous gibberellic acid (GA3) caused defects in meiotic cytokinesis by interfering with radial microtubule array formation resulting in meiotic restitution and 2n pollen production in Populus. A protocol for inducing 2n pollen in Populus with GA3 was established by investigating the effects of the dominant meiotic stage, GA3 concentration, and injection time. The dominant meiotic stage (F = 41.882, P < 0.001) and GA3 injection time (F = 172.466, P < 0.001) had significant effects on the frequency of induced 2n pollen. However, the GA3 concentration (F = 1.391, P = 0.253) did not have a significant effect on the frequency of induced 2n pollen. The highest frequency of GA3-induced 2n pollen (21.37%) was observed when the dominant meiotic stage of the pollen mother cells was prophase Ⅱ and seven injections of 10 μM GA3 were given. Eighteen triploids were generated from GA3-induced 2n pollen. Thus, GA3 can be exploited as a novel mutagen to induce flowering plants to generate diploid male gametes. Our findings provide some new insight into the function of GAs in plants.